PENGUATAN DIMENSI GOTONG ROYONG MELALUI CERITA RAKYAT PADA BUKU CETAK BAHASA INDONESIA FASE C - Jahra Karimatum Minallaahirrahim; Anan Nurir Ridho; Achmad Athoillah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The Pancasila Student Profile embodies the ideal character of Indonesian youth promoted by the Ministry of Education and Culture through six dimensions: faith and piety, independence, mutual cooperation, global diversity, critical reasoning, and creativity. The Pancasila Student Profile Strengthening Project (P5) highlights mutual cooperation through collaboration, caring, and sharing. This qualitative literature study examines how these values are applied in learning, particularly through folklore in the Indonesian language book phase B of the Merdeka Curriculum. Stories like "Darma and Darmin," "Mbah Sadiman, Wonogiri Greening Warrior," and "Legend of the Komodo Princess" showcase mutual cooperation through elements such as teamwork, communication, and social awareness. Folklore serves as an educational tool to instill noble national values, aiming to shape students with strong character, adherence to Pancasila principles, and global competence in line with the spirit of the Independent Curriculum.